Standardization of Forensic Interview with the Child Victim - Büken, Bora; Avgören, Aybike; Dinçer, Ahmet Furkan; Öbek, Ayşe Merve (The Bulletin of Legal Medicine, 2023)
Child abuse which should be considered as a global public health problem, has become increasingly a topical issue due to rapid changes in social life and family structure, migrations. With the child advocacy centers system, which has been organized in our country since 2012, is aimed to manage the forensic and forensic medical evaluation process meticulously with a multidisciplinary approach. There are local differences in the practices of centers located in different provinces. In this study, it is aimed to improve the practice in the field by underlining the main points to be considered during the forensic interview of the cases brought with the claim that they were exposed to sexual abuse. In our study, a standard checklist which will be based on, facilitates the retention of information that can be obtained through family interviews; it will also serve to improve both the self-regulation of the forensic interviewer and the awareness of the judicial authorities. Determinations were made by blending the information in the literature with our professional observations in our practice.
Keywords: Legal medicine, sexual abuse, child abuse; legal medicine; sexual abuse; child abuse